Grandmother's Social Support In Exclusive Breastfeeding Motivation - Rahmawati Ramli; Fatma Jama; Yusrah Taqiyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Grandmother's social support is a form of social interaction in which there is a relationship that gives and receives tangible assistance by grandmothers to mothers in giving exclusive breastfeeding to their babies. This study aims to determine the relationship between grandmother's social support and motivation to exclusively breastfeed mothers at Tomia Utama. The research design was non-experimental quantitative correlational using a proportional stratified random sampling technique with a sample size of 59. The data analysis used was bivariate analysis, chi-square test with ? 0.05. The results showed that social support for grandmothers was good as much as 66.1% with high motivation to give exclusive breastfeeding as much as 94.9%, while social support for grandmothers was not good as much as 33.9% who had low motivation to give exclusive breastfeeding as much as 5.1%. The conclusion of the study is that there is a relationship between grandmother's social support and motivation to exclusively breastfeed the mother.. Suggestion: The need to provide education about the importance of social support for grandmothers and families for the success of exclusive breastfeeding to families and to form breastfeeding support groups.